Kilfenora Cathedral, north wall, tomb niche, hood - O'Donovan, Danielle (My University, 2008)
Pointed hood, comprising, from outside in: roll, free-standing fillet, hollow, scroll, fillet, hollow, roll.
Keywords: Architecture, Gothic -- Ireland; Funerary monuments; Kilfenora (Clare, Ireland); Late Medieval; hood moldings; roll moldings; fillets (moldings); moldings, hollow